On the interpretation of synchronization in EEG hyperscanning studies: a cautionary note - Burgess, Adrian P. (Frontiers in Human Neuroscience, 2013)
EEG Hyperscanning is a method for studying two or more individuals simultaneously with the objective of elucidating how co-variations in their neural activity (i.e. hyperconnectivity) are influenced by their behavioural and social interactions. The aim of this study was to compare the performance of different hyper-connectivity measures using i) simulated data, where the degree of coupling could be systematically manipulated, and ii) individually recorded human EEG combined into pseudo-pairs of participants where no hyper-connections could exist. With simulated data we found that each of the most widely used measures of hyperconnectivity were biased and detected hyper-connections where none existed. With pseudo-pairs of human data we found spurious hyper-connections that arose because there were genuine similarities between the EEG recorded from different people independently but under the same experimental conditions. Specifically, there were systematic differences between experimental conditions in terms of the rhythmicity of the EEG that were common across participants. As any imbalance between experimental conditions in terms of stimulus presentation or movement may affect the rhythmicity of the EEG, this problem could apply in many hyperscanning contexts. Furthermore, as these spurious hyper-connections reflected real similarities between the EEGs, they were not Type-1 errors that could be overcome by some appropriate statistical control. However, some measures that have not previously been used in hyperconnectivity studies, notably the circular correlation co-efficient, were less susceptible to detecting spurious hyper-connections of this type. The reason for this advantage in performance is discussed and the use of the circular correlation co-efficient as an alternative measure of hyperconnectivity is advocated.